Implementasi Media Mock-up Dalam Meningkatkan Antusiasme Belajar Materi Ekosistem Laut Kelas III SDN Ajung 02 - Julia Eva Virdiana; Muhammad Suwignyo Prayogo (CV.ITTC INDONESIA, 2025)
This research examines the effectiveness of using three-dimensional mock-up media to enhance the learning enthusiasm of third-grade students at SDN Ajung 02 regarding marine ecosystem materials. The background of the issue lies in the limited learning media used in the classroom, which can potentially reduce students' interest in learning. Using a qualitative approach and case study design, data were collected through in-depth interviews and observations to understand students' experiences while using this media. The results showed that the application of mock-up media significantly increased student engagement and enthusiasm, which had previously been passive. Students showed greater interest in discussions and collaboration, creating a more dynamic learning environment. These findings highlight the importance of innovative learning media in improving the quality of the learning experience and opening up opportunities for further exploration in the context of elementary education.